2023
DOI: 10.3390/educsci13060537
|View full text |Cite
|
Sign up to set email alerts
|

Academic Success through Engagement and Trust Fostered by Professor Leadership Style

Abstract: This study focused on professor leadership styles and investigated the impacts of various leadership characteristics on student academic performance as well as students’ perceptions of class engagement and trust toward a professor. Using multiple leaderships styles to estimate a model of the relationship between faculty leadership styles and student outcomes provides for a broader view compared to previous research. The empirical results indicated that student perception of class engagement was significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…leadership, have impacted student engagement, trust in themselves, and academic success (Kim et al, 2023). Furthermore, research has indicated that successful student leadership can enhance academic engagement by considering various factors, including active participation, selfefficacy, and motivation (Tortosa-Martínez et al, 2022).…”
Section: Educational Research and Innovation (Eri)mentioning
confidence: 99%
“…leadership, have impacted student engagement, trust in themselves, and academic success (Kim et al, 2023). Furthermore, research has indicated that successful student leadership can enhance academic engagement by considering various factors, including active participation, selfefficacy, and motivation (Tortosa-Martínez et al, 2022).…”
Section: Educational Research and Innovation (Eri)mentioning
confidence: 99%
“…Fostering character development alongside academic achievement is a recognized goal in education [1]. In the context of Islamic education, the Quran offers profound insights into character-building through moral lessons, ethical principles, and practical guidance [2], [3].…”
Section: Introductionmentioning
confidence: 99%